Implementing Task-Based Language Teaching (TBLT) in Teaching Sport English - Sianipar, Rimma (Lembaga Publikasi Ilmiah Dwipantara, 2025)
This study explores the implementation of Task-Based Language Teaching (TBLT) in English instruction for students majoring in Physical Education. The primary objective is to enhance students’ ability to use technical sports terminology, deliver clear instructions, and build speaking confidence in professional contexts. A quasi-experimental design involving 30 participants was employed, comprising a pre-test, TBLT-based instructional intervention, and a post-test to measure fluency, accuracy, and comprehension improvements. Both quantitative data (test scores) and qualitative data (observed student performance) were analyzed. The results indicate significant improvement in students’ ability to communicate training-related instructions effectively. Nevertheless, challenges such as limited vocabulary and issues with sentence structure were observed. The study recommends incorporating structured feedback, supplementary learning materials, and a specialized sports glossary to address these. Overall, TBLT proves to be an effective approach for integrating English language development into sports education. Future studies may consider applying this model to other sports-related disciplines.